She's Hot, for a Politician: The Impact of Objectifying Commentary on Perceived Credibility of Female Candidates. Issue 4 (7th August 2016) - Funk, Michelle E.; Coker, Calvin R.
Abstract : The way female politicians are discussed in traditional and new media may contribute to the way individuals evaluate those candidates. Objectification theory suggests that framing individuals in a way that reduces them to their physical characteristics is detrimental to perceived agency. To that end, an experiment was designed to determine the impact of objectifying comments on the evaluation of female candidates. Researchers created two Facebook feeds discussing a hypothetical female candidate. For both feeds, the discussion focused on the candidate's policy credentials, with one feed containing commentary on the female candidate's body. Aspects of credibility and suitability for office were impacted by objectifying commentary, implying the need for future research directed at the specific impact objectification has on candidate evaluation.